OBJEK PENELITIAN HUKUM KELUARGA - Lia Yuliasih; Mohamad Sar’an; Syahrul Anwar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The object of research constitutes a fundamental element that determines the direction, scope, and depth of legal research. In the field of family law, determining the research object has become increasingly complex due to social transformation, legal reforms, and emerging contemporary issues related to marriage, divorce, child custody, inheritance, domestic violence, and the protection of family members' rights. This study aims to analyze the concept, scope, and appropriate research approaches to family law research objects in order to produce scientific and applicable legal studies. The research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed qualitatively using legal interpretation methods. The findings indicate that the object of family law research extends beyond written legal norms to encompass judicial practices, social realities, Islamic family law, customary law, and human rights perspectives within family relationships. A well-defined research object significantly influences the quality of legal analysis, the suitability of research methods, and the contribution of research to the development of Indonesian family law. Therefore, research objects should be formulated systematically, reflect contemporary legal developments, and provide solutions to current family law issues.